2002
DOI: 10.1074/jbc.m105033200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of p53-dependent Apoptosis Induced by 3-Methylcholanthrene

Abstract: Polycyclic aromatic hydrocarbons (PAHs) such as 3-methylcholanthrene (MC) cause untoward effects including carcinogenesis. Here we investigated the effect of MC on apoptosis. MC induced apoptosis, preceded by serine 15 phosphorylation and accumulation of p53. MC failed to cause apoptosis in p53-deficient MG63 cells, whereas ectopic expression of p53 in MG63 cells restored the response to MC. Therefore, MC-induced apoptosis was dependent on p53. MC also activated p38 mitogen-activated protein kinase (MAPK) at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 38 publications
(32 reference statements)
6
50
0
Order By: Relevance
“…Especially, the phosphorylation of p53 at serine 15 was reported to be a key phosphorylation target during the p53 activation process to apoptotic cell death [16,17]. Of the MAPK families, p53 can be phosphorylated either directly or indirectly by p38 kinase [18][19][20][21] and JNK [22,23]. Compared to several studies on the role of p38 kinase or JNK in p53 regulation, there is less evidence to indicate phosphorylation and/or accumulation of p53 by ERK.…”
Section: Discussionmentioning
confidence: 86%
“…Especially, the phosphorylation of p53 at serine 15 was reported to be a key phosphorylation target during the p53 activation process to apoptotic cell death [16,17]. Of the MAPK families, p53 can be phosphorylated either directly or indirectly by p38 kinase [18][19][20][21] and JNK [22,23]. Compared to several studies on the role of p38 kinase or JNK in p53 regulation, there is less evidence to indicate phosphorylation and/or accumulation of p53 by ERK.…”
Section: Discussionmentioning
confidence: 86%
“…Exposure to chrysotile has been reported to activate ERK in rat pleural mesothelial cells in vitro (Zanella et al 1996) and mouse pulmonary epithelial cells in vivo (Robledo et al 2000), although its effects on p38 and JNK are not known. On the other hand, Ser15 phosphorylation induced by various cellular stimuli such as ultraviolet radiation (Bulavin et al 1999;She et al 2000), cisplatin (Persons et al 2000), L-thyroxine (Shih et al 2001), chromium (Wang and Shi 2001), resveratrol (She et al 2001), and 3-methylcholanthrene (Kwon et al 2002) has been reported to be mediated by ERK and/or p38. However, in the present study, treatment with neither U0126 nor SB203580 suppressed chrysotile-induced Ser15 phosphorylation, indicating it is unlikely that ERK and p38 are responsible for p53 phosphorylation at Ser15 in A549 cells exposed to chrysotile.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the phosphatidylinositol 3-kinase-related kinase (PIKK) family such as DNA-activated protein kinase (DNA-PK) and ataxia-telangiectasia mutated (ATM) have been implicated in the phosphorylation of p53 at Ser15 (Giaccia and Kastan 1998;Lakin and Jackson 1999;Meek 1998). Furthermore, extracellular signal-regulated protein kinase (ERK) and p38, the members of mitogenactivated protein kinase (MAPK), have been reported to induce p53 phosphorylation at Ser15 (Bulavin et al 1999;Kwon et al 2002;Persons et al 2000;She et al 2000She et al , 2001Shih et al 2001;Wang and Shi 2001).…”
mentioning
confidence: 99%
“…18,19 Ser15 phosphorylation could result in the accumulation of p53 via inhibition of MDM2 interaction and protein degradation. 12,20 Both Ser15 and 20 appear to be important at least in the regulation of p53-mediated apoptosis. 21 Analysis of individual mutants revealed that mutations in these specific residues of p53 are primarily responsible for impairment of its apoptotic activity.…”
Section: Control Loading Is Shown By Actinmentioning
confidence: 99%